Short implant versus conventional implant in the posterior atrophic maxilla: A systematic review and meta-analysis - Yogamaya Pradhan; Gunjan Srivastava; Gopal Krishna Choudhury; Pradyumna Kumar Sahoo; Subrat Kumar Padhiary (Wolters Kluwer Medknow Publications, 2024)
Objective: A comparative study undertaken to measure the the marginal bone loss (MBL), implant survival rate, and prosthetic and biological complications among short implants (8 mm or shorter) and conventional implants (longer than 8 mm) in the posterior atrophic maxilla. Materials and Methods: A search in three databases PubMed (Medline), Scopus, and Cochrane was conducted. The present systematic review was registered with identification number CRD42020212805 at the International Prospective Register of Systematic Reviews. Data extraction included the publication year, patients' number and number of implants, implant length and width, MBL, implant survival rate, and biological and mechanical complications. The Cochrane Risk of Bias 1.0 tool was used to assess the risk of bias. A meta-analysis was performed to evaluate the outcome variables. Comparisons for dichotomous variables, such as prosthetic and biological complications and implant survival rate, were done by applying the Mantel-Haenszel method. In contrast, a comparison was made by applying the inverse variance method for continuous variables like MBL. Results: Initially, 618 reports were recognized from electronic database searches. Five randomized controlled trials (RCTs) were included in the meta-analyses regarding the MBL, implant survival rate, and prosthetic complications, while three were included for biological complications. In 5 years of follow-up, no evidence of difference could be found between conventional and short implants for survival rate (risk ratio [RR]: 3.54; 95% confidence interval [CI]: 0.99-12.67; P = 0.05; I2 = 0%). We do not find any evidence of difference for MBL between short implants and conventional implants (mean difference: −0.29; 95% CI: −0.49 to −0.08; P = 0.02; I2 = 65%). Furthermore, no evidence of a difference exists between short and conventional implants for prosthetic complications (RR: 1.56; 95% CI: 0.68-3.55; P = 0.29; I2 = 0%). The biological complications were seen less with short implants (RR: 0.47; 95% CI: 0.24-0.93; P = 0.03; I2 = 0%). Conclusion: The results suggest no significant difference among conventional and short implants regarding survival rate in the posterior atrophic maxilla. The results of this systematic review and meta-analysis suggest that, for a 5-year period of follow-up, short implants are related to rarer biological complications and comparable MBL compared to conventional implants. Despite these promising findings, long-term studies with consistent study designs and clinical protocols are required to appraise the performance and durability of short implants.